THE ROLE OF EMPLOYEE ENGAGEMENT MEDIATION ON THE INFLUENCE OF TALENT MANAGEMENT AND KNOWLEDGE MANAGEMENT ON EMPLOYEE PERFORMANCE - Cecep Syaifullah Syahputra; Marbawi; Ibrahim Qamarius; Faisal Matriadi; Nur Faliza; Yulius Dharma (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This research examines the mediating role of employee engagement on the influence of talent management and knowledge management on employee performance at the BPJS Health Partners Hospital, Langsa City. The sample in this study were employees at the Langsa City Regional Hospital, Cut Meutia Hospital and Cut Nyak Dhien Hospital, Langsa City, Aceh Province, totaling 172 people. Data collected through questionnaires were analyzed using a data analysis method using Structural Equation Modeling (SEM) which was operationalized with the Analysis of Moment Structure (AMOS) tool. The research results show that talent management and knowledge management have a significant effect on employee engagement and employee performance. And employee engagement has a direct effect on employee performance. Then, in testing the indirect effect of employee engagement, it was found to act as a partial mediating variable in the relationship between the influence of talent management and knowledge management on employee performance. It is hoped that the results of this research will be important information for organizational leaders and managers in making policies related to developing employee performance at Langsa City Regional Hospital, Cut Meutia Hospital and Cut Nyak Dhien Hospital, Langsa City, Aceh Province.